EF-Tu From Non-typeable Haemophilus influenzae Is an Immunogenic Surface-Exposed Protein Targeted by Bactericidal Antibodies - Thofte, Oskar; Su, Yu-Ching; Brant, Marta; Littorin, Nils; Duell, Benjamin Luke; Alvarado, Vera; Jalalvand, Farshid; Riesbeck, Kristian (Frontiers in Immunology, 2018)
Non-typeable Haemophilus influenzae (NTHi), a commensal organism in pre-school children, is an oppor¬tunistic pathogen causing respiratory tract infections including acute otitis media. Adults suffering from chronic obstructive pulmonary disease (COPD) are persistently colonized by NTHi. Previous research has suggested that, in some bacterial species, the intracellular elongation factor thermo-unstable (EF-Tu) can moonlight as a surface protein upon host encounter. The aim of this study was to determine whether EF-Tu localizes to the surface of H. influenzae, and if such surface-associated EF-Tu is a target for bactericidal antibodies. Using flow cytometry, transmission immunoelectron microscopy, and epitope mapping, we demonstrated that EF-Tu is exposed at the surface of NTHi, and identified immunodominant epitopes of this protein. Rabbits immunized with whole-cell NTHi produced significantly more immunoglobulin G (IgG) directed against EF-Tu than against the NTHi outer membrane proteins D and F as revealed by enzyme-linked immunosorbent assays. Chemical cleavage of NTHi EF-Tu by cyanogen bromide (CNBr) followed by immunoblotting showed that the immunodominant epitopes were located within the central and C-terminal regions of the protein. Peptide epitope mapping by dot blot analysis further revealed four different immunodominant peptide sequences; EF-Tu41-65, EF-Tu161-185, EF-Tu221-245, and EF-Tu281-305. These epitopes were confirmed to be surface-exposed and accessible by peptide-specific antibodies in flow cytometry. We also analysed whether antibodies raised against NTHi EF-Tu cross-react with other respiratory tract pathogens. Anti-EF-Tu IgG significantly detected EF-Tu on unencapsulated bacteria, including the Gram-negative H. parainfluenzae, H. haemolyticus, Moraxella catarrhalis and various Gram-positive Streptococci of the oral microbiome. In contrast, considerably less EF-Tu was observed at the surface of encapsulated bacteria including H. influenzae serotype b (Hib) and Streptococcus pneumoniae (e.g., serotype 3 and 4). Removal of the capsule, as exemplified by Hib RM804, resulted in increased EF-Tu surface density. Finally, anti-NTHi EF-Tu IgG promoted complement-dependent bacterial killing of NTHi and other unencapsulated Gram-negative bacteria as well as opsonophagocytosis of Gram-positive bacteria. In conclusion, our data demonstrate that NTHi EF-Tu is surface-exposed and recognized by antibodies mediating host innate immunity against NTHi in addition to other unencapsulated respiratory tract bacteria.